Komunitas Kapang Tanah di Lahan Kritis Berkapur DAS Brantas Pada Musim Kemarau - Dian Siswanto; Suharjono Suharjono (Universitas Lambung Mangkurat, 2006)
The lime upland of Brantas River Watershed in East Java Province involve Malang, Blitar, Tulungagung and Trenggalek Regency are dry upland with limestone, low soil organic matter and unproductive. Soil productivity was influenced by microorganism activity that transform soil organic matter and other soil nutrition materials. Soil mold in lime upland of Brantas River Watershed can be used as bioindicator of productivity and soil sustainability. The research aims were to find out soil mold community at dry season in lime upland of The Brantas River Watershed and to know their relation with environmental factors. Chemical and physical parameters observed were soil temperature, sunlight intensity, soil acidity, soil moisture, soil organic matter and water retention capacity, while biological parameters was soil mold abundance. The result showed that soil mold abundances between groups were significantly different. The range of soil mold abundances in Trenggalek were 7x103-2.4x104 propaguls/gram, Tulungagung were 1.8x103-1.0x104 propaguls/gram, Blitar were 7.8x102-4.6x103 propaguls/gram and Malang were 2.8x102-9.0x103 propaguls/gram. Soil mold abundances were not significantly different between village in Malang Regency contain Pagak Village were 2.27x104 propaguls/gram, in Ngembul Village were 7.91x103 propaguls/gram and Banyuurip Village were 3.32x103 propaguls/gram. Soil mold abundances between regency and between village both were not significantly influenced for chemical physic factors. Predominant soil mold in Trenggalek and Blitar were Penicillium while Mucor were dominant in Tulungagung, Penicillium and Phytophtora were codominant in Malang.